Problem-Based Learning-Based E-Module to Enhance Problem-Solving Skills about Pressure Topics: A Preliminary Development - Tri Lestari Budi Asih; Iqbal Ainun Najib; Putri Nanda Agustin; Meirita Sari; Ulinnuha Nur Faizah; Aziza Anggi Maiyanti; Qoimatul Mustaghfiroh; Moch. Ilham Abdul Aziz; M. Abdul Rosyid Sughro; Berliani Naufira; Nabila Nurin Najwa (National Dong Hwa University, 2025)
This study aims to develop an e-module based on problem-based learning to increase students' problem-solving skills regarding material pressure and its application in everyday life. The subject of this research is an 8th-grade student at a junior high school in Bojonegoro. As for the research, the R&D process is 4-D. This is limited only to the 3D phase, namely, until the module's validity. The e-module was validated by four validators: one expert in learning, one in language, one in materials, and one in media. Results validation will be analyzed using a presentation of the results of 4 expert validators. The results from validation by the four validators conclude that the e-module developed its own score (89.4%), which is included in the very valid category. Shows e-module-based problem-based learning on material pressure and its application in daily life. An e-module can be used in science instruction to improve students' problem-solving skills.